Acute Toxicity From Breast Cancer Radiation Using Helical Tomotherapy With a Simultaneous Integrated Boost. (April 2016) - Wojcieszynski, Andrzej P.; Olson, Anna K.; Rong, Yi; Kimple, Randall J.; Yadav, Poonam
Purpose: To evaluate 2 simultaneous integrated boost treatment planning techniques using helical tomotherapy for breast conserving therapy with regard to acute skin toxicity and dosimetry. Methods: Thirty-two patients were studied. The original approach was for 16 patients and incorporated a directional block of the ipsilateral lung and breast. An additional 16 patients were planned for using a modified approach that incorporates a full block of the ipsilateral lung exclusive of 4 cm around the breast. Dose–volume histograms of targets and critical structures were evaluated. Skin toxicity monitoring was performed throughout treatment and follow-up using the Common Terminology Criteria for Adverse Events. Results: Treatment was well tolerated with patients receiving a median dose of 59.36 Gy. Of the 16 patients in both groups, 8 had grade 2 erythema immediately after radiation. On 3-week follow-up, 10 and 7 patients in the original and modified groups showed grade 1 erythema. On 3- and 6-month follow-up, both groups had minimal erythema, with all patients having either grade 0 or 1 symptoms. No grade 2 or 3 toxicities were reported. Mean treatment time was 7.5 and 10.4 minutes using the original and modified methods. Adequate dose coverage was achieved using both methods (V95 = 99.5% and 98%). Mean dose to the heart was 10.5 and 1.8 Gy, respectively ( P < .01). For right-sided tumors, the original and modified plans yielded a mean of 8.8 and 1.1 Gy ( P < .01) versus 11.7 and 2.4 Gy for left-sided tumors ( P < .01). The mean dose to the ipsilateral lung was also significantly lower in the modified plans (11.8 vs 5.0 Gy, P < .01). Conclusions: Tomotherapy is capable of delivering homogeneous treatment plans to the whole breast and lumpectomy cavity using simultaneous integrated boost treatment. Using the treatment methods described herein, extremely low doses to critical structures can be achieved without compromising acute skin toxicity.